Green low-carbon recycled aggregate concrete and preparation method thereof

By treating construction waste with alkali and vinyltrimethoxysilane, and then polymerizing it in a specific monomer solution to form a core-shell structure and a three-dimensional cross-linked network, the problem of insufficient strength and durability of recycled aggregate concrete is solved, and high-strength and low-carbon concrete preparation is achieved.

CN120965222APending Publication Date: 2025-11-18SHAANXI RONGDA TIANSHENG CONCRETE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511127024.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-13
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Recycled aggregates have high porosity, strong water absorption, and low apparent density in concrete, resulting in low strength and poor durability, making it difficult to meet the comprehensive performance requirements of modern construction projects.

Method used

After treating construction waste with alkali, it is then treated with a vinyltrimethoxysilane solution and polymerized in a monomer solution containing methyl methacrylate, glycidyl methacrylate, fluorinated acrylate, and divinylbenzene to form a core-shell structure that fills and seals aggregate cracks, enhances interfacial bonding strength, and incorporates nano-silica and nano-cellulose to form a three-dimensional cross-linked network, thereby improving the strength and durability of concrete.

Benefits of technology

It improves the strength and durability of recycled aggregate concrete, meeting engineering requirements, while reducing cement addition, lowering carbon emissions, and realizing resource recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005545518250000111
    Figure BDA0005545518250000111
  • Figure BDA0005545518250000112
    Figure BDA0005545518250000112
  • Figure BDA0005545518250000121
    Figure BDA0005545518250000121
Patent Text Reader

Abstract

The invention relates to the field of building materials, and particularly discloses recycled aggregate green low-carbon concrete and a preparation method thereof, and the recycled aggregate green low-carbon concrete comprises the following raw materials: cement, slag, fly ash, silica fume, reinforced fibers, water, recycled coarse aggregate, recycled fine aggregate, broken stone, sand, an additive and recycled micro powder; wherein the recycled coarse aggregate and the recycled fine aggregate are obtained by screening recycled aggregate prepared by crushing and modifying construction waste, and the modification treatment comprises the following steps: performing alkali treatment on the construction waste, and then treating the construction waste with a vinyl trimethoxy silane solution; then polymerizing in a monomer solution containing methyl methacrylate, glycidyl methacrylate, fluorinated acrylate and divinyl benzene to form a core-shell structure; the preparation method comprises the following steps: mixing the additive with water to obtain a mixture; mixing the rest raw materials, and stirring and mixing with the mixture to prepare the recycled aggregate green low-carbon concrete. The preparation method has the characteristic that the recycled aggregate concrete with better strength and durability is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of building materials, more particularly, it relates to a recycled aggregate green low-carbon concrete and a preparation method thereof. BACKGROUND

[0002] With the continuous acceleration of urbanization process in China, the construction industry has developed rapidly, and a large amount of construction demolition waste has been generated, among which the concrete waste accounts for a large proportion. The traditional treatment method is landfill or stacking, which not only occupies land resources, but also may cause environmental pollution. In recent years, resource recycling and sustainable development concept have been increasingly valued. As an important achievement of resource utilization of construction waste, recycled aggregate has gradually become a research hotspot.

[0003] Recycled aggregate refers to aggregate material obtained by processing waste concrete through crushing, screening, washing and other processes. Recycled aggregate concrete can significantly reduce the dependence on natural resources and has good environmental effects. However, compared with natural aggregate, recycled aggregate has the characteristics of high porosity, strong water absorption and low apparent density, which limits its application in high-performance concrete to some extent.

[0004] Although the combination of recycled aggregate with industrial by-products such as fly ash, slag, silica fume and the like has been studied to improve its performance, there are still problems of low strength and durability when the content of recycled aggregate is high, which is difficult to meet the comprehensive requirements of modern construction engineering for the performance of concrete.

[0005] Therefore, further research is needed to prepare recycled aggregate-based concrete with higher strength and durability. SUMMARY

[0006] In order to prepare recycled aggregate concrete with better strength and durability, the present application provides a recycled aggregate green low-carbon concrete and a preparation method thereof.

[0007] In the first aspect, the present application provides a recycled aggregate green low-carbon concrete, which adopts the following technical scheme: A recycled aggregate green low-carbon concrete comprises the following raw materials by weight: 280-320 parts of cement, 80-100 parts of slag, 60-70 parts of fly ash, 15-20 parts of silica fume, 8-15 parts of reinforcing fiber, 130-150 parts of water, 600-700 parts of recycled coarse aggregate, 300-400 parts of recycled fine aggregate, 200-250 parts of crushed stone, 450-550 parts of sand, 3-6 parts of additive, and 30-40 parts of recycled micro powder. The recycled coarse aggregate and the recycled fine aggregate are obtained by screening the recycled aggregate prepared by modifying the crushed construction waste, wherein the modification treatment is that the construction waste is treated with alkali, then treated with a vinyl trimethoxysilane solution, and then polymerized in a monomer solution containing methyl methacrylate, glycidyl methacrylate, fluorinated acrylate and divinylbenzene to form a core-shell structure.

[0008] By adopting the technical scheme, the construction waste is first treated with alkali to dissolve silicate impurities on the surface of the aggregate, expose more active siloxane groups, then treated with vinyl trimethoxysilane, and a bond is formed between the silanol and the active siloxane groups on the surface of the aggregate after the hydrolysis of the vinyl trimethoxysilane, thereby introducing vinyl groups, and then polymerized in a monomer solution containing glycidyl methacrylate, fluorinated acrylate and divinylbenzene, so that the unsaturated double bonds in the monomers react with the vinyl groups to form polymer chains on the surface of the recycled aggregate, forming a core-shell structure. The polymer fills the cracks of the aggregate on one hand, and seals the micro-cracks on the surface of the aggregate on the other hand, so that the crack propagation path is blocked, the brittle failure caused by stress concentration is reduced, and the crack resistance is improved. Moreover, the polymer layer has certain toughness and buffering performance, and the durability is improved.

[0009] The glycidyl methacrylate in the monomer solution provides an epoxy group, which can form a ring-opening action with the hydroxyl groups in the cement hydration product to form a chemical bond, thereby enhancing the interfacial bonding strength between the aggregate and the cement matrix, and improving the strength and other mechanical properties of the aggregate in cooperation with the reinforcing fibers. The fluorinated acrylate gives the surface a low surface energy property, greatly improves the water absorption property, and acts as a crosslinking agent to improve the compactness of the shell layer, further achieving crack filling and mechanical property improvement. The divinylbenzene copolymerizes with the glycidyl methacrylate and the fluorinated acrylate to form a three-dimensional crosslinked network, thereby improving the hardness of the shell layer and limiting crack propagation while improving the mechanical properties. Ultimately, the concrete in the application uses recycled aggregate to replace natural aggregate, and the content is relatively large, thereby achieving resource recycling and utilization. The green concrete has higher strength and durability, meets the engineering requirements, and reduces the amount of cement added in cooperation with fly ash and silica ash and other waste, thereby reducing the demand for cement and carbon emissions.

[0010] Optionally, the modification treatment after crushing the construction waste specifically includes the following steps: 1) Soaking the construction waste in a sodium hydroxide solution for 20-30 minutes to obtain alkali-treated aggregate; Mixing the vinyl trimethoxysilane with a mixed solution of ethanol and water, then adjusting the pH value to 4-5, adding the alkali-treated aggregate after stirring for 10-20 minutes, and drying after ultrasonic treatment for 20-30 minutes to obtain pretreated aggregate; 2), methyl methacrylate, methacrylic acid, glycidyl methacrylate, fluorinated acrylate and divinylbenzene are mixed to obtain a mixed monomer, then mixed with a mixed solvent of dihydromyrcenol and propylene glycol monomethyl ether, then sodium dodecyl sulfate and pretreated aggregate are added, then vacuum to-0.08-(-0.05) Mpa, and keep for 30-40 min, then adjust to normal pressure, then heat to 70-80℃, add initiator and react for 3-4h, then filter, wash with acetone and dry to obtain recycled aggregate.

[0011] By adopting the above technical scheme, in the preparation process, the solvent of the monomer solution is dihydromyrcenol, which has the characteristics of high boiling point and low polarity, can reduce the surface tension of the solution, enhance the penetration ability of the monomer to the pores and cracks of the aggregate, and is more helpful to form a polymer, and the addition of propylene glycol monomethyl ether adjusts the polarity of the mixed solution, which is helpful to the mixing and dispersion of the monomer solution, and after adding the pretreated aggregate in the monomer solution, first vacuum negative pressure preservation operation is performed to form a pressure gradient, which drives the monomer solution to penetrate and flow into the pores of the aggregate, enhances the penetration ability of the monomer in the microcracks, and then better polymerization in the microcracks can be realized to fill and seal the microcracks, and the performance of the concrete is improved.

[0012] Optionally, in the modification process of the crushed construction waste, the concentration of the sodium hydroxide solution in step 1) is 5-8wt%, and the amount of the sodium hydroxide solution added is 12-15 times the mass of the construction waste; The amount of vinyltrimethoxysilane added is 5-10wt% of the amount of construction waste, and the volume ratio of ethanol to water is (7-9):1; In step 2), the mass ratio of methyl methacrylate, methacrylic acid, glycidyl methacrylate, fluorinated acrylate and divinylbenzene is 1:(0.4-0.6):(1.5-2):(0.5-0.8):(0.2-0.3); The volume ratio of dihydromyrcenol to propylene glycol monomethyl ether is 1:(2-3), and the amount of the mixed solvent of dihydromyrcenol and propylene glycol monomethyl ether added is 3-5 times the volume of the mixed monomer, the amount of sodium dodecyl sulfate added is 1-3wt% of the mixed solvent, the mass ratio of pretreated aggregate to mixed monomer is 1:(2-3), and the amount of initiator added is 0.5-1wt% of the mixed monomer.

[0013] By adopting the above technical scheme, by controlling the above amount, the performance of the final concrete is better.

[0014] Optionally, in the modification process of the crushed construction waste, a mixture of nano-silicon dioxide and nano-cellulose with a mass ratio of 1:(1.5-1.8) is also added when the pretreated aggregate is added.

[0015] By adopting the technical scheme, when the nano-silicon dioxide and nano-cellulose are added during the preparation of the recycled aggregate, the high pozzolanic activity of the nano-silicon dioxide can not only cause secondary reaction with calcium hydroxide on the surface of the recycled aggregate to generate calcium silicate gel, but also fill micro-cracks and pores of the recycled aggregate through the gel. The rigid rod of the nano-cellulose forms a network structure with cement hydration products on the surface of the recycled aggregate through a hydrogen bond network to inhibit gel flow and reduce water absorption. The addition of the two components can improve the compactness of the recycled aggregate concrete, improve the strength of the recycled aggregate concrete, reduce the water absorption of the recycled aggregate concrete, optimize the interface structure of the recycled aggregate, improve the interface compatibility with the cement matrix, and improve the durability. In addition, the introduction of the methacrylic monomer can introduce a certain amount of carboxyl group, which can form a certain chemical bond with the nano-silicon dioxide and the nano-cellulose, improve the combination between the aggregate, the nano-material filled in the micro-cracks and the outer polymer layer, and further improve the mechanical properties and durability.

[0016] Optionally, during the modification treatment of the crushed construction waste, diethylene triamine is further added to the mixed monomers in step 2), and the mass ratio of methyl methacrylate to diethylene triamine is 1:(0.8-1.2).

[0017] By adopting the technical scheme, diethylene triamine is further added to the mixed monomers as a monomer, which can participate in the copolymerization of the glycidyl methacrylate monomer and other monomers. The amino group of the diethylene triamine can react with the epoxy group of the glycidyl methacrylate to form a cross-linked structure, and the exposed amino group on the surface of the recycled aggregate can form an ionic bond with calcium ions in the cement paste, thereby significantly improving the interface bonding force between the aggregate and the matrix and further improving the performance of the concrete.

[0018] Optionally, the nano-silicon dioxide and the nano-cellulose are added after modification treatment, specifically including the following steps: mixing the nano-silicon dioxide and the nano-cellulose to prepare a to-be-treated mixture, then dispersing the to-be-treated mixture in water, and preparing a mixed suspension after ultrasonic treatment for 10-20 min; Adding sodium hydroxide and phosphate buffer to the mixed suspension to adjust the pH to 8-9, then stirring at 30-40℃ for 1-1.5h to prepare an alkalized suspension; Adding epichlorohydrin dropwise in the alkalized suspension, while adding a mixed solution of cetyltrimethylammonium bromide and isopropyl alcohol, heating to 60-70℃ for 4-5h, then cooling to room temperature, neutralizing, centrifuging and drying to prepare modified nano-silicon dioxide and modified nano-cellulose.

[0019] By adopting the technical scheme, firstly, the nano-silicon dioxide and nano-cellulose are subjected to alkalization treatment to activate the surface groups of the nano-cellulose and nano-silicon dioxide, and then subjected to modification treatment by using epoxy chloropropane, so that the carboxyl or hydroxyl groups on the surface of the nano-material after alkalization attack the ring-opening of the epoxy carbon atoms of the epoxy chloropropane to form ether bonds and introduce epoxy groups, the cetyltrimethylammonium bromide is used as a phase transfer catalyst to promote the transfer of the epoxy chloropropane from the organic phase to the water phase for reaction, and finally the epoxy groups are introduced on the surface of the nano-silicon dioxide and nano-cellulose, which can form ionic bonds with calcium ions and the like in the hydration products on the surface of the aggregate, and form a mutual interpenetrating structure to form a fiber-aggregate matrix composite reinforcement system, thereby improving the strength of the concrete, and the three-dimensional network structure formed can effectively hinder the penetration of chloride ions and the like, reduce the interface microcracks, and improve the impermeability and durability.

[0020] Moreover, the epoxy groups in the nano-material can also form chemical bonds with the amino groups in the monomer mixture, thereby realizing the modification and cross-linking structure of the recycled aggregate, and obviously improving the defects of low strength and high water absorption rate of the recycled aggregate caused by crushing, and further improving the strength and durability of the concrete.

[0021] Optionally, when the nano-silicon dioxide and nano-cellulose are subjected to modification treatment, the water is added in an amount of 2-3 times the mass of the nano-cellulose. The addition mass ratio of the treated mixture to the epoxy chloropropane is 1:(8-10), the addition amount of the cetyltrimethylammonium bromide is 1-2 wwt% of the treated mixture, and the addition amount of the isopropyl alcohol is 20-30 wt% of the treated mixture. Phosphate buffer (such as sodium dihydrogen phosphate-sodium hydrogen phosphate at pH 8.0) 0.1-0.5 mol / L NaOH solution Optionally, the reinforcing fiber is glass fiber.

[0022] By adopting the technical scheme, the glass fiber surface contains silicon hydroxyl groups, and the epoxy groups and amino groups on the surface of the recycled aggregate form chemical bonds to promote the interface bonding between the recycled aggregate and the cement group, thereby improving the performance of the concrete.

[0023] Optionally, the additive includes a polycarboxylate superplasticizer.

[0024] Optionally, the particle size of the gravel is a continuous gradation of 5-20 mm, and the sand is sand with a fineness modulus of 2.6-3.0.

[0025] In a second aspect, the application provides a preparation method of recycled aggregate green low-carbon concrete, which adopts the following technical scheme: A preparation method of recycled aggregate green low-carbon concrete, comprising the following steps: Mixing the additive with water to obtain a mixture; The remaining raw materials are mixed and stirred with the mixture to obtain the recycled aggregate green low-carbon concrete.

[0026] By adopting the technical scheme, the method is simple and convenient.

[0027] In summary, the application has the following beneficial effects: In the application, the construction waste is first subjected to alkali treatment to dissolve silicate impurities on the surface of the aggregate, expose more active siloxane groups, and then subjected to vinyl trimethoxysilane treatment. After hydrolysis of the vinyl trimethoxysilane, silanol forms a bond with the active siloxane groups on the surface of the aggregate, thereby introducing vinyl groups. Then, the aggregate is polymerized in a monomer solution containing glycidyl methacrylate, fluorinated acrylate and divinylbenzene. The unsaturated double bonds in the above monomers react with the vinyl groups to form polymer chains on the surface of the recycled aggregate, forming a core-shell structure. The polymer fills the cracks in the aggregate and seals the microcracks on the surface of the aggregate, thereby blocking the crack propagation path and reducing brittle failure caused by stress concentration, thereby improving the crack resistance of the recycled aggregate. In addition, the polymer layer has certain toughness and buffering performance, thereby improving the durability of the recycled aggregate. DETAILED DESCRIPTION

[0028] The application is further described in detail below in conjunction with examples. It should be particularly noted that: in the following examples, the specific conditions are not specified, and the conventional conditions or the conditions recommended by the manufacturer are used. In the following examples, the raw materials used can be obtained from ordinary commercial sources unless otherwise specified.

[0029] In the following examples, the recycled micro-powder is a construction waste fine powder with a D50 of less than or equal to 15 microns. The cement used is P.O 42.5 ordinary portland cement; the fly ash used is F I-grade fly ash; the slag used is S95-grade slag; and the polycarboxylate superplasticizer used is a polycarboxylate superplasticizer from Jinan Quanchi New Materials Co., Ltd.

[0030] In the following examples, the particle size of the crushed stone is a continuous gradation of 5-20 mm, the sand used is sand with a fineness modulus of 2.6-3.0; the recycled coarse aggregate and the recycled fine aggregate are obtained by screening the recycled aggregate prepared by crushing and modifying the construction waste. The particle size of the recycled coarse aggregate is a continuous particle size of 5-15 mm, and the particle size of the recycled fine aggregate is a continuous particle size of 0.15-3.0 mm.

[0031] In the following preparation examples, the fluorinated acrylate is specifically a perfluorooctyl ethyl methacrylate from Sichuan Xieai Fluorine Technology Co., Ltd.; and the nanocellulose used is CNF dry powder of type Darl-1 from Hubei Darli Chemical Co., Ltd.

[0032] In the following preparation examples, the ultrasonic treatment has an ultrasonic power of 50 W.

[0033] The following preparation example is a preparation example of a recycled aggregate Preparation Example 1 A method for preparing a recycled aggregate, comprising the following steps: 1) crushing construction waste to form aggregate of 0.10mm-20mm, then dipping and treating in a sodium hydroxide solution with a mass concentration of 6% for 25min, the sodium hydroxide solution being added in an amount of 13 times the mass of the construction waste to obtain alkali aggregate; mixing a mixed solution of vinyl trimethoxysilane, ethanol and water, the volume ratio of ethanol and water being 8:1, the amount of ethanol added being 4.5 times the mass of the vinyl trimethoxysilane, and the amount of vinyl trimethoxysilane added being 8wt% of the amount of the construction waste; then adjusting the pH value to 4.5, adding the obtained alkali aggregate after stirring for 15min, ultrasonic treatment for 25min, and drying to obtain pretreated aggregate; 2) mixing methyl methacrylate, methacrylic acid, glycidyl methacrylate, fluorinated acrylate and divinylbenzene according to an adding mass ratio of 1:0.5:1.8:0.6:0.25 to obtain mixed monomers; mixing dihydromyrcenol and propylene glycol monomethyl ether according to a volume ratio of 1:2.5 to obtain a mixed solvent, then mixing the obtained mixed monomers with the mixed solvent, adding sodium dodecyl sulfate and pretreated aggregate, then vacuumizing to-0.06Mpa and maintaining for 35min, adjusting to normal pressure, then increasing the temperature to 75℃, adding an initiator (azobisisobutyronitrile) and reacting for 3.5h, then filtering, washing with acetone and drying to obtain recycled aggregate; wherein the volume ratio of dihydromyrcenol and propylene glycol monomethyl ether is 1:2.5, the amount of the mixed solvent of dihydromyrcenol and propylene glycol monomethyl ether added is 4 times the volume of the mixed monomers, the amount of sodium dodecyl sulfate added is 2wt% of the mixed solvent, the adding mass ratio of pretreated aggregate to mixed monomers is 1:2.5, and the amount of initiator added is 0.8wt% of the mixed monomers.

[0034] Preparation Example 2 A method for preparing a recycled aggregate, comprising the following steps: 1) crushing construction waste to form aggregate of 0.10mm-20mm, then dipping and treating in a sodium hydroxide solution with a mass concentration of 5% for 20min, the sodium hydroxide solution being added in an amount of 12 times the mass of the construction waste to obtain alkali aggregate; mixing a mixed solution of vinyl trimethoxysilane, ethanol and water, the volume ratio of ethanol and water being 7:1, the amount of ethanol added being 4 times the mass of the vinyl trimethoxysilane, and the amount of vinyl trimethoxysilane added being 5wt% of the amount of the construction waste; Then the pH value is adjusted to 4, the alkali aggregate obtained is added after stirring for 10 min, and the pretreated aggregate is prepared after drying after ultrasonic treatment for 20 min; 2) The methyl methacrylate, methacrylic acid, glycidyl methacrylate, fluorinated acrylate and divinylbenzene are mixed in an additive mass ratio of 1:0.4:1.5:0.5:0.2 to prepare a mixed monomer; The dihydrosafrol and propylene glycol monomethyl ether are mixed in a volume ratio of 1:2 to prepare a mixed solvent, then the mixed monomer prepared is mixed with the mixed solvent, then sodium dodecyl sulfate and the pretreated aggregate are added, then vacuum is drawn to-0.08 Mpa, and the pressure is adjusted to normal pressure after maintaining for 30 min, then the temperature is raised to 70 DEG C, the initiator (azobisisobutyronitrile) is added, and reaction is carried out for 4 h, then the regenerated aggregate is prepared after filtering, washing with acetone and drying; The volume ratio of dihydrosafrol and propylene glycol monomethyl ether is 1:2, the mixed solvent of dihydrosafrol and propylene glycol monomethyl ether is added in an amount of 3 times the volume of the mixed monomer, the sodium dodecyl sulfate is added in an amount of 1 wt% of the mixed solvent, the pretreated aggregate is added in a mass ratio of 1:2 to the mixed monomer, and the initiator is added in an amount of 0.5 wt% of the mixed monomer.

[0035] Preparation Example 3 A method for preparing a regenerated aggregate, comprising the following steps: 1) Building waste is crushed to form aggregate with a size of 0.10 mm-20 mm, then the aggregate is immersed in a sodium hydroxide solution with a mass concentration of 8% for 30 min, and the sodium hydroxide solution is added in an amount of 15 times the mass of the building waste to prepare alkali aggregate; The mixed solution of vinyltrimethoxysilane, ethanol and water is mixed, the volume ratio of ethanol and water is 9:1, the amount of ethanol added is 5 times the mass of the vinyltrimethoxysilane, and the amount of vinyltrimethoxysilane added is 10 wt% of the amount of the building waste; Then the pH value is adjusted to 5, the alkali aggregate obtained is added after stirring for 20 min, and the pretreated aggregate is prepared after drying after ultrasonic treatment for 30 min; 2) The methyl methacrylate, methacrylic acid, glycidyl methacrylate, fluorinated acrylate and divinylbenzene are mixed in an additive mass ratio of 1:0.6:2:0.8:0.3 to prepare a mixed monomer; The dihydrosafrol and propylene glycol monomethyl ether are mixed in a volume ratio of 1:3 to prepare a mixed solvent, then the mixed monomer prepared is mixed with the mixed solvent, then sodium dodecyl sulfate and the pretreated aggregate are added, then vacuum is drawn to-0.05 Mpa, and the pressure is adjusted to normal pressure after maintaining for 40 min, then the temperature is raised to 80 DEG C, the initiator (azobisisobutyronitrile) is added, and reaction is carried out for 3 h, then the regenerated aggregate is prepared after filtering, washing with acetone and drying; The volume ratio of dihydroterpineol and propylene glycol monomethyl ether is 1:3, the adding amount of the mixed solvent of dihydroterpineol and propylene glycol monomethyl ether is 5 times the volume of the mixed monomer, the adding amount of sodium dodecyl sulfate is 3wt% of the mixed solvent, the adding mass ratio of the pretreated aggregate to the mixed monomer is 1:3, and the adding amount of the initiator is 1wt% of the mixed monomer.

[0036] Preparation Example 4 A preparation method of recycled aggregate is performed according to the method in Preparation Example 1, except that in step 2), the pretreated aggregate is added together with modified nano composite powder, the modified nano composite powder is obtained by modifying the nano composite powder obtained by mixing nano silicon dioxide and nano cellulose at a mass ratio of 1:1.6, and the adding amount of the modified nano composite powder is 8wt% of the pretreated aggregate, wherein the modification of the nano composite powder specifically includes the following steps: a. Mix nano silicon dioxide and nano cellulose at a mass ratio of 1:1.6 to obtain nano composite powder as a to-be-treated mixture, then disperse the to-be-treated mixture in water, and after ultrasonic treatment for 15 min, obtain a mixed suspension, and the adding amount of water is 2.5 times the mass of nano cellulose; b. Add 0.3mol / L of sodium hydroxide and phosphate buffer (specifically, sodium dihydrogen phosphate-sodium hydrogen phosphate buffer with pH of 8.0) into the mixed suspension to adjust the pH of the mixed suspension to 8.5, then stir at 35℃ for 70min to obtain an alkalized suspension; c. Add dropwise epoxy chloropropane into the alkalized suspension, and add a mixed solution of cetyltrimethylammonium bromide and isopropyl alcohol at the same time, heat to 65℃ and react for 4.5h, then cool to room temperature, neutralize, centrifugalize and dry to obtain modified nano silicon dioxide and modified nano cellulose.

[0037] In step c, the adding mass ratio of the to-be-treated mixture to epoxy chloropropane is 1:9, the adding amount of cetyltrimethylammonium bromide is 1.5wwt% of the to-be-treated mixture, and the adding amount of isopropyl alcohol is 25wt% of the to-be-treated mixture.

[0038] Preparation Example 5 A preparation method of recycled aggregate is performed according to the method in Preparation Example 1, except that in step 2), the pretreated aggregate is added together with modified nano composite powder, the modified nano composite powder is obtained by modifying the nano composite powder obtained by mixing nano silicon dioxide and nano cellulose at a mass ratio of 1:1.5, and the adding amount of the modified nano composite powder is 6wt% of the pretreated aggregate, wherein the modification of the nano composite powder specifically includes the following steps: a. The nanosilica and nanocellulose are mixed in a mass ratio of 1:1.5 to prepare a nanocomposite powder as a mixture to be treated, and then the mixture to be treated is dispersed in water to prepare a mixed suspension after ultrasonic treatment for 10 min, and the amount of water added is 2 times the mass of the nanocellulose; b. 0.3 mol / L of sodium hydroxide and a phosphate buffer (specifically, a sodium dihydrogen phosphate-disodium hydrogen phosphate buffer with a pH of 8.0) are added to the mixed suspension to adjust the pH of the mixed suspension to 8, and then the mixed suspension is stirred at 30°C for 1.5 h to prepare an alkalized suspension; c. Epichlorohydrin is added dropwise to the alkalized suspension, and a mixed solution of cetyltrimethylammonium bromide and isopropanol is added at the same time, the temperature is raised to 60°C, and the reaction is carried out for 5 h, and then the reaction mixture is cooled to room temperature, neutralized, centrifuged, and dried to prepare modified nanosilica and modified nanocellulose.

[0039] In step c, the mass ratio of the mixture to be treated to epichlorohydrin is 1:8, the amount of cetyltrimethylammonium bromide added is 1 wwt% of the mixture to be treated, and the amount of isopropanol added is 20 wt% of the mixture to be treated.

[0040] Preparation Example 6 A method for preparing recycled aggregate is performed according to the method in Preparation Example 1, except that in step 2), the modified nanocomposite powder is added to the pretreated aggregate, the modified nanocomposite powder is obtained by modifying the nanocomposite powder mixed from nanosilica and nanocellulose in a mass ratio of 1:1.8, and the amount of the modified nanocomposite powder added is 10 wt% of the pretreated aggregate, wherein the modification of the nanocomposite powder specifically includes the following steps: a. The nanosilica and nanocellulose are mixed in a mass ratio of 1:1.8 to prepare a nanocomposite powder as a mixture to be treated, and then the mixture to be treated is dispersed in water to prepare a mixed suspension after ultrasonic treatment for 20 min, and the amount of water added is 3 times the mass of the nanocellulose; b. 0.3 mol / L of sodium hydroxide and a phosphate buffer (specifically, a sodium dihydrogen phosphate-disodium hydrogen phosphate buffer with a pH of 8.0) are added to the mixed suspension to adjust the pH of the mixed suspension to 9, and then the mixed suspension is stirred at 40°C for 1 h to prepare an alkalized suspension; c. Epichlorohydrin is added dropwise to the alkalized suspension, and a mixed solution of cetyltrimethylammonium bromide and isopropanol is added at the same time, the temperature is raised to 70°C, and the reaction is carried out for 4 h, and then the reaction mixture is cooled to room temperature, neutralized, centrifuged, and dried to prepare modified nanosilica and modified nanocellulose.

[0041] In step c, the mass ratio of the mixture to be treated to the added epichlorohydrin is 1:10, the added amount of cetyltrimethylammonium bromide is 2 wwt% of the mixture to be treated, and the added amount of isopropyl alcohol is 30 wwt% of the mixture to be treated.

[0042] Preparation Example 7 A method for preparing recycled aggregate is performed according to the method in Preparation Example 1, except that in step 2), the pre-processed aggregate is added with nano-composite powder, the nano-composite powder is obtained by mixing nano-silica and nano-cellulose at a mass ratio of 1:1.6, and the added amount of the nano-composite powder is 8 wwt% of the pre-processed aggregate.

[0043] Preparation Example 8 A method for preparing recycled aggregate is performed according to the method in Preparation Example 1, except that in step 2), the monomer mixture is further added with diethylene triamine, and the added mass ratio of methyl methacrylate to diethylene triamine is 1:1.

[0044] Preparation Example 9 A method for preparing recycled aggregate is performed according to the method in Preparation Example 1, except that in step 2), the monomer mixture is further added with diethylene triamine, and the added mass ratio of methyl methacrylate to diethylene triamine is 1:0.8.

[0045] Preparation Example 10 A method for preparing recycled aggregate is performed according to the method in Preparation Example 1, except that in step 2), the monomer mixture is further added with diethylene triamine, and the added mass ratio of methyl methacrylate to diethylene triamine is 1:1.2.

[0046] Comparative Preparation Example 1 A method for preparing recycled aggregate is performed according to the method in Preparation Example 1, except that in step 2), the monomer mixture is not added with glycidyl methacrylate.

[0047] Comparative Preparation Example 2 A method for preparing recycled aggregate is performed according to the method in Preparation Example 1, except that in step 2), the monomer mixture is not added with divinylbenzene.

[0048] Comparative Preparation Example 3 A method for preparing recycled aggregate is performed according to the method in Preparation Example 1, except that in step 2), the monomer mixture is not added with fluorinated acrylate.

[0049] Comparative Preparation Example 4 A method for preparing recycled aggregate is performed according to the method in Preparation Example 1, except that in step 1), the vinyltrimethoxysilane is replaced with KH-550.

[0050] Example 1 A preparation method of recycled aggregate green low-carbon concrete comprises the following steps: 5 kg of an admixture is mixed with 140 kg of water to obtain a mixture, the admixture being a polycarboxylate superplasticizer; 300 kg of cement, 90 kg of slag, 65 kg of fly ash, 18 kg of silica fume, 12 kg of reinforcing fiber, 650 kg of recycled coarse aggregate, 350 kg of recycled fine aggregate, 230 kg of crushed stone, 500 kg of sand, and 35 kg of recycled micro powder are mixed and then stirred with the mixture to obtain the recycled aggregate green low-carbon concrete.

[0051] The reinforcing fiber is glass fiber, the particle size of the crushed stone is 5-20 mm of continuous gradation, the sand is medium sand with a fineness modulus of 2.6-3.0, the cement is P.O 42.5 ordinary Portland cement, the fly ash is FI-grade fly ash, the slag is S95-grade slag, the recycled coarse aggregate and the recycled fine aggregate are obtained by screening the recycled aggregate obtained in the preparation example 1, and the particle size of the recycled coarse aggregate is 5-15 mm of continuous gradation, and the particle size of the recycled fine aggregate is 0.15-3.0 mm of continuous gradation.

[0052] Example 2 A preparation method of recycled aggregate green low-carbon concrete comprises the following steps: 3 kg of an admixture is mixed with 130 kg of water to obtain a mixture, the admixture being a polycarboxylate superplasticizer; 280 kg of cement, 80 kg of slag, 60 kg of fly ash, 15 kg of silica fume, 8 kg of reinforcing fiber, 600 kg of recycled coarse aggregate, 300 kg of recycled fine aggregate, 200 kg of crushed stone, 450 kg of sand, and 30 kg of recycled micro powder are mixed and then stirred with the mixture to obtain the recycled aggregate green low-carbon concrete.

[0053] The reinforcing fiber is glass fiber, the particle size of the crushed stone is 5-20 mm of continuous gradation, the sand is medium sand with a fineness modulus of 2.6-3.0, the cement is P.O 42.5 ordinary Portland cement, the fly ash is FI-grade fly ash, the slag is S95-grade slag, the recycled coarse aggregate and the recycled fine aggregate are obtained by screening the recycled aggregate obtained in the preparation example 2, and the particle size of the recycled coarse aggregate is 5-15 mm of continuous gradation, and the particle size of the recycled fine aggregate is 0.15-3.0 mm of continuous gradation.

[0054] Example 3 A preparation method of recycled aggregate green low-carbon concrete comprises the following steps: 6 kg of an admixture is mixed with 150 kg of water to obtain a mixture, the admixture being a polycarboxylate superplasticizer; 320 kg of cement, 100 kg of slag, 70 kg of fly ash, 20 kg of silica fume, 15 kg of reinforcing fiber, 700 kg of recycled coarse aggregate, 400 kg of recycled fine aggregate, 250 kg of crushed stone, 550 kg of sand, and 40 kg of recycled micro powder are mixed and stirred with the mixture to prepare a recycled aggregate green low-carbon concrete.

[0055] The reinforcing fiber is selected from glass fiber, the particle size of the crushed stone is a continuous gradation of 5-20 mm, the sand is selected from medium sand with a fineness modulus of 2.6-3.0, the cement is selected from P.O 42.5 ordinary portland cement, the fly ash is selected from FI grade fly ash, the slag is selected from S95 grade slag, and the recycled coarse aggregate and the recycled fine aggregate are the recycled coarse aggregate with a continuous particle size of 5-15 mm and the recycled fine aggregate with a continuous particle size of 0.15-3.0 mm obtained by screening the recycled aggregate prepared in Preparation Example 3.

[0056] Examples 4-10 A method for preparing a recycled aggregate green low-carbon concrete is performed according to the method in Example 1, except that the recycled coarse aggregate and the recycled fine aggregate are selected from the recycled coarse aggregate and the recycled fine aggregate obtained by screening the recycled aggregate prepared in Preparation Examples 4-10, respectively.

[0057] Comparative Examples 1-4 A method for preparing a recycled aggregate green low-carbon concrete is performed according to the method in Example 1, except that the recycled coarse aggregate and the recycled fine aggregate are selected from the recycled coarse aggregate and the recycled fine aggregate obtained by screening the recycled aggregate prepared in Comparative Preparation Examples 1-4, respectively.

[0058] Performance detection The concrete prepared in the examples and comparative examples of the present application is tested according to the standard of GB / T50081-2019 "Standard Test Methods for Physical and Mechanical Properties of Concrete" to form a 100mmx100mmx100mm sample, and the compressive strength after 28 days of curing is detected, and the detection results are shown in Table 1 below; In addition, the water penetration height of the concrete under the condition of 1.5MPa water pressure is tested according to the standard of the water penetration test-water height method in GB / T50082-2009 "Standard Test Methods for Long-Term Performance and Durability of Ordinary Concrete", to characterize the anti-permeability performance, and the detection results are shown in Table 1 below.

[0059] The mass loss rate under 50 cycles of freeze-thaw conditions (freezing temperature is -20℃, and thawing temperature is 22℃) is detected according to GB / T50082-2009 "Standard Test Methods for Long-Term Performance and Durability of Ordinary Concrete", and the detection results are shown in Table 1.

[0060] Table 1: Table 1 (continued): Referring to the detection results in Table 1 above, the concrete prepared based on the recycled aggregate in the embodiments of the present application has excellent mechanical properties and good durability. In combination with the detection results of Example 1 and Examples 4-6, when the pretreated aggregate is added in the preparation process of the recycled aggregate and the modified nano composite powder is also added, the strength and durability are both significantly improved. The filling effect of the nano composite powder helps to improve the strength of the aggregate and reduce the water absorption rate, and the introduction of the epoxy group helps to improve the interfacial bonding between the aggregate and the polymer layer, and better improve the performance of the concrete. In combination with the detection results of Example 7, when the nano composite powder is not modified by epoxy and is directly added in Example 7, the performance is slightly lower than that of Example 4 but still better than that of Example 1. It can be seen that the addition of the nano composite powder helps to fill the microcracks, and the introduction of the epoxy group further improves the anchoring and interfacial bonding force, and further improves the performance.

[0061] In combination with the detection results of Example 1 and Examples 8-10, it can be seen that when the diethylenetriamine is also added in the monomer mixture, the performance is also better than that of Example 1. The addition of diethylenetriamine as a monomer helps to introduce amino groups in the polymer layer, and then form better chemical bonding with the cement matrix, and also form better chemical bonding with the aggregate, thereby improving the performance of the concrete. In combination with the detection results of Comparative Examples 1-3, when only methacrylic acid is selected as the monomer in the monomer mixture and no fluorine-containing monomer or epoxy-based monomer is added, the strength and durability are both reduced. In particular, in Comparative Example 1, the mechanical properties are reduced when no epoxy monomer is added, in Comparative Example 2, the mechanical properties and durability are both reduced when no divinylbenzene is added, and in Comparative Example, the impermeability and freeze-thaw resistance are reduced when no fluorine-containing monomer is added. In combination with the performance of Comparative Example 4 when the vinyl silane is replaced by an equal amount of ordinary silane coupling agent, the performance is also significantly reduced. The introduction of the vinyl monomer in the vinyl silane helps to realize in-situ polymerization of the subsequent monomer on the surface of the aggregate and polymer filling, thereby improving the performance.

[0062] The specific embodiments are merely an explanation of the present application, and are not a limitation of the present application. Those skilled in the art can make modifications to the embodiments without creative contribution after reading the present specification, and the modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A recycled aggregate green low-carbon concrete, characterized by, The following raw materials are included by weight parts: 280-320 parts of cement, 80-100 parts of slag, 60-70 parts of fly ash, 15-20 parts of silica fume, 8-15 parts of reinforcing fiber, 130-150 parts of water, 600-700 parts of recycled coarse aggregate, 300-400 parts of recycled fine aggregate, 200-250 parts of gravel, 450-550 parts of sand, 3-6 parts of admixture, 30-40 parts of recycled micro powder; The recycled coarse aggregate and the recycled fine aggregate are obtained by screening the recycled aggregate prepared by crushing and modifying the construction waste, wherein the modification treatment is that the construction waste is treated with alkali and then treated with a vinyltrimethoxysilane solution, and then polymerized in a monomer solution containing methyl methacrylate, glycidyl methacrylate, fluorinated acrylate and divinylbenzene to form a core-shell structure.

2. The recycled aggregate green low-carbon concrete according to claim 1, characterized in that: The crushing and modification treatment of the construction waste specifically includes the following steps: 1) The construction waste is immersed in a sodium hydroxide solution for 20-30 min to obtain alkali-treated aggregate; The vinyltrimethoxysilane is mixed with a mixed solution of ethanol and water, and then the pH value is adjusted to 4-5. After stirring for 10-20 min, the alkali-treated aggregate is added, ultrasonic treatment is performed for 20-30 min, and then drying is performed to obtain pretreated aggregate; 2) Methyl methacrylate, methacrylic acid, glycidyl methacrylate, fluorinated acrylate and divinylbenzene are mixed to obtain a mixed monomer, which is then mixed with a mixed solvent of dihydromyrcenol and propylene glycol monomethyl ether, and then sodium dodecyl sulfate and pretreated aggregate are added. Then, vacuum is applied to-0.08 to (-0.05) Mpa and maintained for 30-40 min, then adjusted to normal pressure, then heated to 70-80℃, added initiator and reacted for 3-4h, then filtered, washed with acetone and dried to obtain recycled aggregate.

3. The recycled aggregate green low-carbon concrete according to claim 2, characterized in that: In the process of crushing and modification treatment of the construction waste, the concentration of the sodium hydroxide solution in step 1) is 5-8wt%, and the amount of sodium hydroxide solution added is 12-15 times the mass of the construction waste; The amount of vinyltrimethoxysilane added is 5-10wt% of the amount of construction waste, and the volume ratio of ethanol to water is (7-9):1; In step 2), the mass ratio of methyl methacrylate, methacrylic acid, glycidyl methacrylate, fluorinated acrylate and divinylbenzene is 1:(0.4-0.6):(1.5-2):(0.5-0.8):(0.2-0.3); The volume ratio of dihydromyrcenol to propylene glycol monomethyl ether is 1:(2-3), and the amount of mixed solvent of dihydromyrcenol and propylene glycol monomethyl ether added is 3-5 times the volume of the mixed monomer, the amount of sodium dodecyl sulfate added is 1-3wt% of the mixed solvent, the mass ratio of pretreated aggregate to mixed monomer is 1:(2-3), and the amount of initiator added is 0.5-1wt% of the mixed monomer.

4. The recycled aggregate green low-carbon concrete according to claim 2, characterized in that: In the process of crushing and modification treatment of the construction waste, a mixture of nano-silicon dioxide and nano-cellulose with a mass ratio of 1:(1.5-1.8) is also added when the pretreated aggregate is added.

5. The recycled aggregate green low-carbon concrete according to claim 2, characterized in that: In the modification treatment process of the crushed construction waste, diethylene triamine is further added in the mixed monomers in step 2), and the mass ratio of methyl methacrylate to diethylene triamine is 1: (0.8-1.2).

6. The recycled aggregate green low-carbon concrete according to claim 4, characterized in that: The modified nano-silica and nano-cellulose are added after modification treatment, and the process comprises the following steps: The nano-silica and nano-cellulose are mixed to obtain a mixture to be treated, and then dispersed in water to obtain a mixed suspension after ultrasonic treatment for 10-20 min; Sodium hydroxide and phosphate buffer are added to the mixed suspension to adjust the pH to 8-9, and then stirred at 30-40℃ for 1-1.5 h to obtain an alkalized suspension; Epoxy chloropropane is added dropwise in the alkalized suspension, and a mixed solution of cetyltrimethylammonium bromide and isopropyl alcohol is added at the same time, and then heated to 60-70℃ for reaction for 4-5 h, and then cooled to room temperature, neutralized, centrifuged and dried to obtain modified nano-silica and modified nano-cellulose.

7. The recycled aggregate green low-carbon concrete according to claim 6, characterized in that: The amount of water added during the modification treatment of nano-silica and nano-cellulose is 2-3 times the mass of nano-cellulose; The mass ratio of the mixture to be treated to epoxy chloropropane is 1: (8-10), the amount of cetyltrimethylammonium bromide added is 1-2 wwt% of the mixture to be treated, and the amount of isopropyl alcohol added is 20-30 wt% of the mixture to be treated.

8. The recycled aggregate green low-carbon concrete according to claim 1, characterized in that: The reinforcing fiber is glass fiber.

9. The recycled aggregate green low-carbon concrete according to claim 1, characterized in that: The admixture includes polycarboxylic acid water reducing agent, the particle size of the crushed stone is 5-20 mm of continuous gradation, and the sand is sand with a fineness modulus of 2.6-3.

0.

10. The method for preparing green low-carbon recycled aggregate concrete according to any one of claims 1-9, characterized in that: The process comprises the following steps: The admixture is mixed with water to obtain a mixture; The remaining raw materials are mixed and stirred with the mixture to obtain recycled aggregate green low-carbon concrete.